Opioids in non-cancer pain: Lesson from the West and experience from Malaysia - Zin, Che Suraya (2019)
Opioid analgesics have long been used as the gold standard to treat severe pain, most notably for acute pain and in palliative care. The use of opioids in chronic non-cancer pain (CNCP) has been much more controversial due to lack of robust evidence supporting the long term opioid use in CNCP, as the majority of the randomized controlled trials are of short duration. Despite the controversy, the use of opioids for CNCP has increased markedly in North America, with patients often receiving doses far in excess of those originally suggested for treatment. The increasing use of opioids has been paralleled by a dramatic rise in opioid-related mortality. More than 16,000 people now die annually of opioid-related causes in the United States alone, and similar trends have emerged in Canada, Australia, and Europe. Many of these deaths could be avoided by more judicious prescribing of opioids in patients with chronic pain. Lessons need to be learned from the widespread opioid prescribing, in order to be able to keep patients more safely protected from the inevitable consequences of opioids.